The Writings of St Paul: Annotated Texts, Reception and Criticism, 2nd edition. Edited by Wayne A. Meeks and John T. Fitzgerald - Morgan, Robert (The journal of theological studies, 2009)
The first edition of this title, by Wayne Meeks alone (1973), was a brilliant and creative selection of views of Paul in the Early Church, a touch of Luther, and much more from the nineteenth and twentieth centuries, from Kierkegaard to Meeks's own epilogue. This was mainly German because ‘it is a simple fact that the overwhelming majority of works which have had wide and lasting influence on international critical scholarship for the past century have been by German authors’ (p. xxi). Meeks also performed a service by translating ‘several pivotal essays’ into English. The texts of the thirteen Pauline letters are reproduced in their probable chronological order using the RSV, each introduced and annotated in an admirably compact manner.